2016
DOI: 10.1186/s13063-016-1428-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and omega-3 fatty acid supplements in children with autism spectrum disorder: a study protocol for a factorial randomised, double-blind, placebo-controlled trial

Abstract: BackgroundThere is strong mechanistic evidence to suggest that vitamin D and omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFAs), specifically docosahexaenoic acid (DHA), have the potential to significantly improve the symptoms of autism spectrum disorder (ASD). However, there are no trials that have measured the effect of both vitamin D and n-3 LCPUFA supplementation on autism severity symptoms. The objective of this 2 × 2 factorial trial is to investigate the effect of vitamin D, n-3 LCPUFAs or a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…A Cochrane review did not find any evidence of effects of omega-3 FA in ASD [338]; by contrast, a recent study by Mazahery et al [339] have shown that either vitamin D, DHA, or both are effective; the trial would reveal a noninvasive approach to managing ASD symptoms.…”
Section: Autism -Paradigms Recent Research and Clinical Applicationsmentioning
confidence: 91%
“…A Cochrane review did not find any evidence of effects of omega-3 FA in ASD [338]; by contrast, a recent study by Mazahery et al [339] have shown that either vitamin D, DHA, or both are effective; the trial would reveal a noninvasive approach to managing ASD symptoms.…”
Section: Autism -Paradigms Recent Research and Clinical Applicationsmentioning
confidence: 91%
“…This study was conducted as an exploratory analysis of the data from the Vitamin D and Omega-3 LCPUFA in Autism (VIDOMA) trial. A detailed description of the design of the VIDOMA trial and its main results have been published [43,49,50]. The protocol was registered with the Australian New Zealand Clinical Trial Registry, ACTRN12615000144516, and the ethical approval was granted by Health and Disability Ethics Committee, NZ, Reference NO.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Children who met the initial inclusion criteria had a blood draw and were screened for nutritional deficiencies (including vitamin D, iron and vitamin B 12 deficiencies). Prior to randomisation, those deficiencies were addressed (refer to [49] and Table 1 for the list of deficiencies and the strategies used to address those deficiencies). Children were then randomly assigned to one of four treatment groups: vitamin D 3 (VID, 2000 IU/day), omega-3 LCPUFA (OM, 722 mg/day DHA), both (VIDOM), or placebo.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bibliography review has shown evidence of the relationship between vitamin D and folate levels and the diagnosis of autism in children (Altun et al, 2018 ; Frye et al, 2018 ; Garipardic et al, 2017 ; Gong et al, 2014 ; Mazahery et al, 2016 ; Sun et al, 2016 ). In fact, a recent meta-analysis assessed the relationship between vitamin D levels and autism, including studies published through November 2019 (Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%